The South Asian Association for Regional Cooperation (SAARC) : an emerging collaboration architecture - Saez, Lawrence, 1965- (Global institutions, 2011)
"This work aims to examine the institutional structure, objectives, and effectiveness of the SAARC in its role as South Asia's leading regional institution"--